Organic dispersion of polyaniline and single-walled carbon nanotubes and polyblends with poly(methyl methacrylate). (27th October 2017) - Farrell, Thomas; Wang, Kan; Lin, Cheng-Wei; Kaner, Richard B.
Abstract: Traditionally, in situ polymerization has been used to make polymer-carbon nanotube composites. Here, we report a simple method of mixing polyaniline with single-walled carbon nanotubes in a variety of organic solvents via ultrasonication. The maximum loading fraction of SWCNTs in the composites is determined by the conformation of the polyaniline chains. The type of solvent used has the greatest influence on the conformation of the polyaniline chains. Furthermore, the composites can be easily blended with poly(methyl methacrylate) (PMMA), to form polyblends. The electrical conductivities and transparencies of the polyblend films are reported. Graphical abstract: Highlights: Polyaniline forms composites with SWCNTs via simple ultrasonication. The polyaniline/SWCNT composites can easily form blends with other polymers. Polymer/SWCNT composites form conductive and transparent films via spin-coating. Conformation of polyaniline chains is determined by the solvent used.